Evolution of Japan's foreign policy to Africa and the TICAD process - Carvalho, Pedro Raposo de Medeiros, 1969- (2009)
Lusíada. Política internacional e segurança. - ISSN 1647-1342. - S. 1, n. 2 (2009). - p. 121-144.